Essentials of contemporary management - Jones, Gareth R. (McGraw-Hill, 2007)
Jones and George are dedicated to the challenge of "Making It Real" for students. As a team, they are uniquely qualified to write about the organizational challenges facing today's managers. No other author team in the management discipline matches their combined research and text-writing experience. Essentials of Management concisely surveys current management theories and research. Through a variety of real world examples from small, medium, and large companies the reader learns how those ideas are used by practicing managers. The organization of this text follows the mainstream functional approach of planning, organizing, leading, and controlling; but the content is flexible and encourages instructors to use the organization they are most comfortable with. The themes of diversity, ethics, and information technology are clearly evident through in-text examples, photographs, "unboxed" stories, and the end-of-chapter material - all areas of importance that truly serve to bring to life the workplace realities that today's student will encounter in the course of a career.